2012
DOI: 10.1039/c2jm31213a
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of polycaprolactone substrates using collagen-conjugated poly(methacrylic acid) brushes for the regulation of cell proliferation and endothelialisation

Abstract: The incorporation and presentation of cell recognition ligands on the surfaces of biodegradable bloodvessel implants to promote endothelialisation is considered to be a promising approach to prevent platelet aggregation and hence thrombogenesis. In this study, cell-adhesive collagen was covalently immobilised onto polycaprolactone (PCL) substrates via surface-initiated atom transfer radical polymerization (ATRP) to improve cell-material interactions. Functional polymer brushes of poly(methacrylic acid) (P(MAA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 46 publications
6
89
0
Order By: Relevance
“…Among the numerous approaches to improve cell seeding on the biomaterial surface, the most common techniques involve the use of a biomolecular coating such as collagen, chondroitin sulfate, sulfated hyaluronan, diamines, heparin, and RGD motif [28]. However, these coating methods experience limitations in regard to practical applications due to lack of stability and the requirement for complicated or expensive procedures [29-31]. Thus, the HGCS-PDA material with DA incorporated can be a good alternative candidate for these conventional methods.…”
Section: Discussionmentioning
confidence: 99%
“…Among the numerous approaches to improve cell seeding on the biomaterial surface, the most common techniques involve the use of a biomolecular coating such as collagen, chondroitin sulfate, sulfated hyaluronan, diamines, heparin, and RGD motif [28]. However, these coating methods experience limitations in regard to practical applications due to lack of stability and the requirement for complicated or expensive procedures [29-31]. Thus, the HGCS-PDA material with DA incorporated can be a good alternative candidate for these conventional methods.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with conventional surfaces, a higher degree of biomolecule functionalization is achieved with P(M)AA brushes due to their 3D architecture and abundant carboxyl groups. Bovine serum albumin (BSA), 37 39,45,61,72,81,85,128,129 Fundamental research devoted to the NHS/EDC process has revealed unique aspects of this process for 3D P(M)AA brushes. A comparative study revealed that, while the major species obtained after activation was NHS ester for PAA brushes (as is the usual case), the major species for PMAA brushes was anhydride.…”
Section: Immobilization Of Biomoleculesmentioning
confidence: 99%
“…From the Figure 9 it was observed that the hydrogels containing the BCP of different ionic block lengths showed good cell proliferation compared to the control sample. It is reported that the cell proliferation in some way depends on the surface hydrophilicity and the micro roughness of the surface 51 . As shown in Figure S5(b) on formation of the ionic BCPs the WCA value reduced from 78° (homo PCL) to 32° for cationic BCP and 36° for the anionic BCP.…”
Section: In-vitro Cell Cytotoxicity Assaymentioning
confidence: 99%